Mechanical Restraint in Nursing Homes in Brazil: a cross-sectional study - Romulo Delvalle; Rosimere Ferreira Santana; Ariana Kassiadou Menezes; Keila Mara Cassiano; Ana Carolina Siqueira de Carvalho; Patrícia de Fátima Augusto Barros
ABSTRACT Objective: to estimate the mechanical restraint prevalence in Nursing Homes in Brazil and the factors associated with its performance. Methods: this cross-sectional study was carried out in 14 institutions, with a final sample of 443 elderly people. Mechanical restraint was considered as a dependent variable. Results: there was a 7.45% prevalence of mechanical restraint considering bed rails and 3.84% without considering bed rails. Main justification for restraint use was risk of falls (66.7%), and restraint duration was 24 hours (84.8%). The factors associated with the dependent variable were: wandering (p=0.000); MMSE, with cognitive loss (p=0.000); Katz Index, with dependence for Activities of Daily Living (p=0.000); and Alzheimer's comorbidity (p=0.001) Conclusion: prevalence was lower than international studies, but there was an association with worsening of wandering, dependence, cognitive worsening, and Alzheimer's Disease, showing the need for alternative interventions to mechanical restraint.